Use of Opuntia ficus-indica (L.) Mill extracts from Brazilian Caatinga as an alternative of natural moisturizer in cosmetic formulations - Gabriel Azevedo de Brito Damasceno; Rebeca Manuelle Alexandre da Costa Silva; Júlia Morais Fernandes; Elissa Arantes Ostrosky; Silvana Maria Zucolotto Langassner; Márcio Ferrari (Brazilian Journal of Pharmaceutical Sciences)
ABSTRACT The aim of this work was the obtainment of Opuntia fícus-indica (L.) Mill extract for the development of cosmetic formulations and in vivo evaluation of its moisturizing effects. The formulations were tested for preliminary and accelerated stability. Organoleptic characteristics, pH values and rheological behavior were assessed. The evaluation of moisturizing efficacy of the emulsions formulated with 3.0% of Polyacrylamide (and) C13-14 Isoparaffin (and) Laureth-7 containing 1.0 and 3.0% of O. ficus-indica hydroglycolic extract (EHG001) was performed using the capacitance method (Corneometer(r)) and the transepidermal water loss - TEWL evaluation (Tewameter(r)). The emulsions formulated were stable, exhibiting pseudoplastic and thixotropic behavior. The results of evaluation of moisturizing efficacy showed increased skin hydration after five hours by mainly increasing the skin barrier effect. The formulations containing 1.0 and 3.0% of EHG001 enhanced the skin barrier effect by reducing TEWL up to four hours after application. The results observed suggest that O. ficus-indica hydroglycolic extract may act through a humectant and occlusion mechanism.